Strength properties of Oriented Strand Board (OSB) from cinnamomum iners with different strand geometry, resin content and density / Ismail Abd Rahim, Mohd Zulkhairi Zulkafly and Marzuki Morad - Abd Rahim, Ismail; Zulkafly, Mohd Zulkhairi; Morad, Marzuki (2008)
Structural strand composite literature often cites strand geometry, resin content and level of density as a factor controlling mechanical properties. This effect is quantified through strand width and length to composite properties. The research presented here examines the effect of strand length and width separately by maintaining a single nominal thickness for three nominal strand lengths and widths, 74.80 mm and 8.67 for 8 mm size of strand and 75.67 mm and 27.33 mm for 15 mm size of strand respectively. The properties were assessed for both the parallel and transverse directions of each board. Besides that, this study about strength properties of Oriented Strand Board (OSB) from Cinnamomum iners at 600 kg/m3 density with 5% and 9% resin content. This study also show the properties of (OSB) at 500 kg/m3 and 700 kg/m3 with 5 % resin content and 15mm size of strands.